Chromosome microarray analysis combined with karyotype analysis is a powerful tool for the detection in pregnant women with high-risk indicators - Guanhua Qian; Liuyun Cai; Hong Yao; Xiaojing Dong (BMC, 2023)
Abstract Background Karyotype analysis and fluorescence in situ hybridization (FISH) are commonly used for prenatal diagnosis, however they have many disadvantages. Chromosome microarray analysis (CMA) has the potential to overcome these disadvantages. This study aimed to evaluate the clinical value of CMA in the diagnosis of fetal chromosomal anomalies in southwest of China. Methods A total of 3336 samples of amniotic fluid or umbilical cord blood from pregnant women with high-risk indicators at our center in southwest of China from June 2018 to January 2023 were included in the retrospective analysis. 3222 cases tested by CMA and karyotyping, 114 cases only tested by CMA. Results 3336 samples divided into 2911 cases with single and 425 cases with multiple high-risk indicators. The aneuploidy and pathogenic/likely pathogenic copy number variations (CNVs) of 2911 cases with single high-risk indicator were 4.43% (129/2911) and 2.44% (71/2911) respectively; the aneuploidy and pathogenic/likely pathogenic CNVs of 425 cases with multiple high-risk indicators were 6.82% (29/425) and 2.12% (9/425) respectively. The rate of aneuploidy increased significantly with pregnancy age or NT value. The detection rate of aneuploidy on cases with AMA combined NT ≥ 2.5 mm was significantly higher than that in cases only with AMA (p < 0.001); the detection rate of aneuploidy and pathogenic/likely pathogenic CNVs in cases with AMA combined NIPT high-risk were higher than that in cases only with AMA (p < 0.001, p < 0.05). Conclusions The combined application of CMA and karyotyping were recommended in prenatal diagnosis for providing a scientific and accurate genetic diagnosis and improving the quality of prenatal genetic counseling.